Cost-effective and extensible LLC-resonant voltage-multiplier-based differential power processing optimizer for mismatched photovoltaic systems. (1st September 2021) - Wang, Xue; Wen, Huiqing; Chu, Guanying; Zhou, Jiafeng
Highlights: LLC-resonant voltage-multiplier-based DPP optimizer is presented with low cost and good extensibility. The switch count is limited to two for long-string photovoltaic systems. The output power under severe shading scenario can be improved up to 32.9%. The presented DPP optimizer cost for four-module-series-connection PV systems can be reduced up to 45.41%. Abstract: Mismatched photovoltaic (PV) power systems due to the shadow effect will result in serious consequences such as reduced output power, hot spot problem, and low reliability. As one promising architecture to address this issue, differential power processing (DPP) optimizer has been extensively discussed to improve the actual energy yield through the charge redistribution among PV elements such as modules or sub-modules. However, since a large number of hardware components must be added in the conventional DPP optimizer, high cost and poor extensibility have become the bottleneck for the practical application of DPP technique in long-string photovoltaic systems. This paper presents an LLC-resonant voltage-multiplier-based DPP (LLC-VM-DPP) optimizer to address these problems. Specifically, the LLC resonant inverter with two switches is operating as a voltage equalizer to compensate the power reduction of shaded PV elements. The switch count is limited to two even for long-string photovoltaic systems. No feedback is required for the control implementation. Thus, the overall system performance such as the cost, circuit complexity, extensibility, power density, and efficiency can be improved. Simulation and experimental evaluation of the LLC-VM-DPP architecture for four-module-series-connection PV systems under different shading scenarios was carried out. Detailed power loss analysis was presented. With the LLC-VM-DPP architecture, the measured output power under severe shading scenario can be improved up to 32.9% while the presented DPP optimizer cost for four-module-series-connection PV systems can be reduced up to 45.41%.